Randomised controlled trials of mood stabilisers for people with autism spectrum disorder: systematic review and meta-analysis. Issue 2 (24th March 2022) - Limbu, Bharati; Deb, Shoumitro; Roy, Meera; Lee, Rachel; Roy, Ashok; Taiwo, Oluwafemi
Abstract : Background: Despite the widespread use of psychotropic medications in people with autism spectrum disorder (ASD), there is limited evidence to suggest that psychotropic medications including mood stabilisers are effective in individuals with ASD. Aims: To carry out a systematic review and meta-analysis of randomised controlled trials (RCTs) that assessed the effectiveness of mood stabilisers in people with ASD. Method: We searched the following databases: Cochrane Library, MEDLINE, Embase, CINAHL, PsycINFO, ERIC, DARE, and ClinicalTrials.gov. In addition, we hand-searched 12 relevant journals. We used the Cochrane Risk of Bias and Jadad scores to assess the quality of included RCTs. We carried out a meta-analysis using a random-effects model. Results: We included eight RCTs (four on valproate, two on levetiracetam, and one each on lamotrigine and topiramate) that included a total of 310 people with ASD, primarily children. Outcomes were based on core and associated ASD symptoms including irritability and aggression but not bipolar disorder. Only two small studies (25%) from the same group showed definite superiority over placebo and one over psychoeducation alone. Meta-analysis of pooled data on the Aberrant Behaviour Checklist-irritability, Clinical Global Impression Scale-improvement, and Overt Aggression Scale (OAS)/OAS-modified did not show any significant inter-group difference. The rates of adverse effects did not show any significant inter-group difference. Conclusions: Given the methodological flaws in the included studies and the contradictory findings, it is difficult to draw any definitive conclusion about the effectiveness of mood stabilisers to treat either ASD core symptoms or associated behaviours. Robust large-scale RCTs are needed in the future to address this issue. PROSPERO registration: CRD42021255467 on 18 May 2021.